Emergent quantum Majorana metal from a chiral spin liquid - Penghao Zhu; Shi Feng; Kang Wang; Tao Xiang; Nandini Trivedi (Nature Communications)
Abstract We propose a mechanism to explain the emergence of an intermediate gapless spin liquid phase in the antiferromagnetic Kitaev model in an externally applied magnetic field, sandwiched between the well-known gapped chiral spin liquid and the gapped partially polarized phase. We propose that, in moderate fields, π-fluxes nucleate in the ground state and trap Majorana zero modes. As these fluxes proliferate with increasing field, the Majorana zero modes overlap creating an emergent $${{\mathbb{Z}}}_{2}$$ Z 2 quantum Majorana metallic state with a “Fermi surface” at zero energy. We further show that the Majorana spectral function captures the dynamical spin and dimer correlations obtained by the infinite Projected Entangled Pair States method, thereby validating our variational approach.